Recreational runners who recovered from COVID-19 show different running kinetics and muscle activities compared with healthy controls - Jafarnezhadgero, A. A.; Hamlabadi, M. P.; Sajedi, H.; Granacher, U. (Gait and Posture, 2021)
Background: Social isolation through quarantine represents an effective means to prevent COVID-19 infection. A negative side-effect of quarantine is low physical activity. Research question: What are the differences of running kinetics and muscle activities of recreational runners with a history of COVID-19 versus healthy controls? Methods: Forty men and women aged 20-30 years participated in this study and were divided into two experimental groups. Group 1 (age: 24.1 ± 2.9) consisted of participants with a history of COVID-19 (COVID group) and group 2 (age: 24.2 ± 2.7) of healthy age and sex-matched controls (controls). Both groups were tested for their running kinetics using a force plate and electromyographic activities (i.e., tibialis anterior [TA], gastrocnemius medialis [Gas-M], biceps femoris [BF], semitendinosus [ST], vastus lateralis [VL], vastus medialis [VM], rectus femoris [RF], gluteus medius [Glut-M]). Results: Results demonstrated higher peak vertical (p = 0.029; d=0.788) and medial (p = 0.004; d=1.119) ground reaction forces (GRFs) during push-off in COVID individuals compared with controls. Moreover, higher peak lateral GRFs were found during heel contact (p = 0.001; d=1.536) in the COVID group. COVID-19 individuals showed a shorter time-to-reach the peak vertical (p = 0.001; d=3.779) and posterior GRFs (p = 0.005; d=1.099) during heel contact. Moreover, the COVID group showed higher Gas-M (p = 0.007; d=1.109) and lower VM activity (p = 0.026; d=0.811) at heel contact. Significance: Different running kinetics and muscle activities were found in COVID-19 individuals versus healthy controls. Therefore, practitioners and therapists are advised to implement balance and/or strength training to improve lower limbs alignment and mediolateral control during dynamic movements in runners who recovered from COVID-19.